2020
DOI: 10.1016/j.jhydrol.2020.125473
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of future SWOT-based river elevations, surface extent observations and discharge estimations into uncertain global hydrological models

Abstract: Global estimates of river dynamics are needed in order to manage water resources, mainly in developing countries where in-situ observation is limited. Remote sensors such as nadir altimeters can complement ground data. Current altimeters miss however a large number of continental surface water bodies. This issue will be largely resolved by the future Surface Water and Ocean Topography (SWOT) mission, thanks to its wide swath altimeter. SWOT will provide almost globally two-dimensional water elevation maps for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 109 publications
(155 reference statements)
0
37
0
Order By: Relevance
“…More recently, Wongchuig‐Correa et al. (2020) evaluated the assimilation of synthetic SWOT observations of water surface elevation, width, and the estimated discharge into a continental scale hydrologic model which explicitly represents hydrodynamic routing through a basin. Wongchuig‐Correa and coauthors not only observed that the assimilation of SWOT discharge was beneficial, but also that the assimilation of discharge, water surface elevation, and width together yielded better improvements than assimilating just water surface elevation, width or discharge alone.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Wongchuig‐Correa et al. (2020) evaluated the assimilation of synthetic SWOT observations of water surface elevation, width, and the estimated discharge into a continental scale hydrologic model which explicitly represents hydrodynamic routing through a basin. Wongchuig‐Correa and coauthors not only observed that the assimilation of SWOT discharge was beneficial, but also that the assimilation of discharge, water surface elevation, and width together yielded better improvements than assimilating just water surface elevation, width or discharge alone.…”
Section: Resultsmentioning
confidence: 99%
“…Ref. [25] reports that the main sources of global hydrologic model discharge errors are precipitation and water budget parameters uncertainty in their experiment. It is likely that climatic forcings such as these, in addition to the calibrated parameters, also impact KGE values here.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [25] investigates the potential of SWOT to correct hydrologic models on a global scale through data assimilation, finding model discharge errors reduced by 40%. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances, models are highly dependent on observations. Observations are used as forcing to hydrological models (e.g., precipitation) and validation (De Paiva et al., 2013; Getirana, Kumar, et al., 2017), calibration (Guimberteau et al., 2012) and assimilation (Wongchuig‐Correa et al., 2020) data. Accurate and long‐period observation‐based estimates are needed for improving the models and deepening our understanding of the water cycle.…”
Section: Introductionmentioning
confidence: 99%